Elective surgery for aortic abdominal aneurysm: comparison of English outcomes with those elsewhere. Issue 3 (26th February 2007) - Filipovic, Miodrag; Goldacre, Michael J; Gill, Leicester
Abstract : Introduction: The aim of this study was to quantify mortality after elective repair of abdominal aortic aneurysm (AAA) in England, and to compare English case fatality rates (CFRs) with those reported in the literature. Patients and methods: English Hospital Episode Statistics (HES) for the financial years 1998/9 to 2001/2, linked to death data, were analysed. A systematic literature search was undertaken to identify studies reporting CFRs after elective AAA surgery. The CFR in England was compared with these studies by using confidence intervals on the CFRs and funnel plot techniques. Results: In the English study, elective repair of AAA was performed on 11 338 patients of whom 771 died within 30 days after surgery (6.8%). The literature search found 66 studies: 34 reported mortality rates that were within the 99% confidence limits of the English rates, 31 below, and one study above. Discussion: The CFR after elective surgical repair in England within 30 days of operation (6.8%) was higher than expected from the literature. Differences between England and other countries in quality of care is one possible explanation for the findings, but other explanations are possible and are discussed.